Justice Oliver Wendell Holmes law and the inner self - White, George Edward 1941- (Oxford Univ. Press, 1993)
By any measure, Oliver Wendell Holmes, Jr., led a full and remarkable life. He was tall and exceptionally attractive, especially as he aged, with piercing eyes, a shock of white hair, and a prominent military moustache. He was the son of a famous father (Oliver Wendell Holmes, Sr., renowned for "The Autocrat of the Breakfast Table"), a thrice-wounded veteran of the Civil War, a Harvard-educated member of Brahmin Boston, the acquaintance of Longfellow, Lowell, and Emerson, and for a time a close friend of William James. He wrote one of the classic works of American legal scholarship, The Common Law, and he served with distinction for thirty years on the Supreme Court of the United States. He was actively involved in the Court's work into his nineties. In Justice Oliver Wendell Holmes: Law and the Inner Self, G. Edward White, the acclaimed biographer of Earl Warren and one of America's most esteemed legal scholars, provides a rounded portrait of this remarkable jurist
Keywords: Holmes, Oliver Wendell <1841-1935>; Holmes, Oliver Wendell -- 1841-1935; Juges - Etats-Unis - Biographies; Rechters; Judges -- United States -- Biography; USA; Biografie